The Use of Outsourced Accounting Service and Its Impact on SMEs Performance - Fadilla Cahyaningtyas; Mega Noerman Ningtyas (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2020)
This research was about the important contribution of SMEs to Indonesian economy in reality and their weak management accounting functions. This research aimed to find out the factors influencing SMEs’ decision to use outsourced accounting advisory services and the effect of such use towards SMEs’ performance as from Transaction Cost Economics (TCE) and Resource Based View (RBV) perspectives. In this research, the population was comprised of manufacturing SMEs ini Malang. The researchers then took the sample using purposive sampling method. Meanwhile, the criteria to determine the sample were based on the definition of SME in Indonesia. Furthermore, the researchers conducted survey by distributing 270 questionnaires to collect the data. Using SEM (AMOS) analysis, the researchers successfully figured out that asset specification, environment uncertainty, technical competence, and competition level acted as major factors that affected SMEs’ decision to use outsourced accounting services. Meanwhile, the researchers found that behavior uncertainty and trust in accountants did not have significant impact on such SMEs’ decision. The result of SEM analysis showed that outsourced accounting advisory services significantly provided positive effect on SMEs’ performance